2015
DOI: 10.1002/stem.1894
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 and PRMT8 Regulate Retinoic Acid-Dependent Neuronal Differentiation with Implications to Neuropathology

Abstract: Retinoids are morphogens and have been implicated in cell fate commitment of embryonic stem cells (ESCs) to neurons. Their effects are mediated by RAR and RXR nuclear receptors. However, transcriptional cofactors required for cell and gene-specific retinoid signaling are not known. Here we show that protein arginine methyl transferase (PRMT) 1 and 8 have key roles in determining retinoid regulated gene expression and cellular specification in a multistage neuronal differentiation model of murine ESCs. PRMT1 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 70 publications
(91 reference statements)
2
23
0
2
Order By: Relevance
“…Interestingly, we also observed an increase in tsGlnCTG association with pro-differentiation transcripts such as Myl3, CD44, and Dkk3 [24][25][26] (Fig 4D 0 and Dataset EV5). The fact that pro-neuronal genes were not enriched by 5 0 -tsRNAs compared with other lineages suggests the intriguing possibility that during neural lineage differentiation triggered by RA [27], tsGlnCTG may gain an additional function in targeting and regulating transcripts driving non-neuronal pathways. The fact that pro-neuronal genes were not enriched by 5 0 -tsRNAs compared with other lineages suggests the intriguing possibility that during neural lineage differentiation triggered by RA [27], tsGlnCTG may gain an additional function in targeting and regulating transcripts driving non-neuronal pathways.…”
Section: Of 18mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we also observed an increase in tsGlnCTG association with pro-differentiation transcripts such as Myl3, CD44, and Dkk3 [24][25][26] (Fig 4D 0 and Dataset EV5). The fact that pro-neuronal genes were not enriched by 5 0 -tsRNAs compared with other lineages suggests the intriguing possibility that during neural lineage differentiation triggered by RA [27], tsGlnCTG may gain an additional function in targeting and regulating transcripts driving non-neuronal pathways. The fact that pro-neuronal genes were not enriched by 5 0 -tsRNAs compared with other lineages suggests the intriguing possibility that during neural lineage differentiation triggered by RA [27], tsGlnCTG may gain an additional function in targeting and regulating transcripts driving non-neuronal pathways.…”
Section: Of 18mentioning
confidence: 99%
“…While initially counter intuitive, upon closer examination of these transcripts, we noticed a significant association (P value < 0.05) with genes involved in skeletal, cardiovascular, and blood vessel development compared with neuronal lineage (Dataset EV6). The fact that pro-neuronal genes were not enriched by 5 0 -tsRNAs compared with other lineages suggests the intriguing possibility that during neural lineage differentiation triggered by RA [27], tsGlnCTG may gain an additional function in targeting and regulating transcripts driving non-neuronal pathways. Interestingly, when we compared the transcripts that associated with 5 0 -tsRNAs in the RA condition with transcripts that were either up-or downregulated in RA-treated cells transfected with ASOs, we observed minimal overlap ( Fig EV4G).…”
Section: Of 18mentioning
confidence: 99%
“…While initially counter intuitive, upon closer examination of those transcripts, we noticed significant association towards genes involved in skeletal, cardiovascular, and blood vessel development compared to neuronal lineage (Table S4). Together, these data suggest that during neural lineage differentiation triggered by RA (Simandi et al, 2015), tsGlnCTG may gain an additional function in targeting and regulating the stability of transcripts driving non-neuronal pathways thus facilitating neuronal differentiation apart from regulating basic cellular processes. Furthermore, retrospective analysis of Brachyury expression (a neural mesodermal marker) revealed that it was unchanged upon ASO-mediated knockdown of tsRNAs ( Fig.…”
Section: Tsrnas Regulate Specific Targets Through Their Protein Intermentioning
confidence: 82%
“…Prmt6 regulates both pluripotency genes and differentiation markers to participate in the maintenance of ES cell identity (Lee et al, 2012). Although Prmt1 provides the bulk of the protein arginine methylation activity within cells (Bedford & Clarke, 2009;Simandi et al, 2015) and Prmt1-null mice die at E6.5 (Pawlak et al, 2000), little is known about the role of Prmt1 in early embryonic development.…”
Section: Introductionmentioning
confidence: 99%